The effect of S/Se ratio on the properties of Cu2CdGe(SxSe1−x)4 microcrystalline powders for photovoltaic applications. (October 2020) - Li, X.; Pilvet, M.; Timmo, K.; Grossberg, M.; Mikli, V.; Kauk-Kuusik, M.
Highlights: A continuous series of Cu2 CdGe(Sx Se1−x )4 powders have been investigated. Pure δ-solid solutions were observed in the limited alloy region 0 < x < 0.1. The band gap energy of Cu2 CdGe(Sx Se1−x )4 increased from 1.27 to 2.04 eV by increasing the sulfur content. The highest PCE of 6.4% for Cu2 CdGe(Sx Se1−x )4 (x = 0.2) monograin layer solar cells have been achieved. Abstract: The morphology, structural and compositional properties of Cu2 CdGe(Sx Se1−x )4 (x = 0; 0.05; 0.1; 0.15; 0.2; 0.4; 0.6; 0.8; 1) microcrystalline powders and solar cells based on these powders are investigated by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy as well as current-voltage and external quantum efficiency (EQE) methods. XRD analysis showed that all Cu2 CdGe(Sx Se1−x )4 solid solutions synthesized at 700 °C crystallize in orthorhombic structure ( Pmn21) regardless of S/Se ratio. Cu2 CdGe(Sx Se1−x )4 solid solutions (x = 0; 0.05; 0.1) synthesized at 500 °C have a tetragonal structure ( I- 42 m ). Cu2 CdGe(Sx Se1−x )4 solid solution with x = 0.15 has a mixture of two crystal structures. Lattice parameters decrease by increasing the S-content in the solid solutions. The median crystal size decreased with the increasing S content in the Cu2 CdGe(Sx Se1−x )4 powders about two times. According to EQE measurements of the solar cells, the band gap of the Cu2 CdGe(Sx Se1−x )4 absorber material shifted towards shorter wavelengths with increasing S content, growing from 1.27 eV for x = 0 to 2.04 eV for x = 1. In this study, Cu2 CdGe(Sx Se1−x )4 solid solution with x = 0.2 enabled the highest power conversion efficiency of 6.4% for monograin layer solar cells with parameters VOC  = 724 mV, JSC  = 18.8 mA/cm 2 and FF = 46.9%.